MULTIVARIATE ANALYSIS WITH EMPHASIS OF HER2/NEU EXPRESSION ON OVARIAN TUMORS IN A TERTIARY CARE HOSPITAL - PRAVEENA T; PAVITRA K; MADHAVI K (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the study was to evaluate immunohistochemical expression of HER2/NEU in ovarian tumors. Whether we can correlate HER2/NEU expression with the age of the patient, tumor size, histopathological type, and histopathological grade of the tumor. Methods: Retrospective study was carried out for 2 years, ovarian specimens were received, grossing was done and evaluated with hematoxylin-eosin staining on 40 cases, and immunostaining with HER2/NEU was done on 32 cases of surface epithelial tumors. Results: Out of 32 cases, HER2/NEU positivity was seen in 18 (56.5%) cases, and negativity was seen in 14 (43.5%) cases. Fifteen cases (46.8%) were serous type and 17 cases (53.2%) were mucinous serous ovarian tumors. A total of 18 cases had shown HER2/NEU positivity. In serous tumors, 0/+1 score was seen in 5(15%) benign (serous cystadenomas + serous adenofibromas) tumors, and in 1(3.1%) borderline, +2 score was seen in 2 (6.3%) borderline and +3 score was seen in 7 (21.8%) serous cystadenocarcinomas. In mucinous tumors, 6 (18%) benign (mucinous cystadenomas) and 2(6.3%) borderline tumors showed 0/+1 score. Score +2 was assigned to 5 (13.8%) benign (mucinous cystadenomas) tumors, 2(6.3%) mucinous cystadenocarcinomas and 2 (6.3%) mucinous cystadenocarcinomas shown +3 positivity Conclusion: HER2/neu expression needs further evaluation to emerge as a prognostic indicator, which indicates disease progression, survival rate, and whether its overexpression can be correlated with the staging of the tumor or not in the near future. Prognostic significance of HER2/NEU is well established in breast carcinomas, unlike in ovarian carcinomas, which warranted further studies to establish its role.